White matter integrity and functional predictors of response to repetitive transcranial magnetic stimulation for posttraumatic stress disorder and major depression. Issue 11 (2nd September 2019) - Barredo, Jennifer; Bellone, John A.; Edwards, Melissa; Carpenter, Linda L.; Correia, Stephen; Philip, Noah S.
Abstract: Background: Recent evidence suggests that therapeutic repetitive transcranial magnetic stimulation (TMS) is an effective treatment for pharmacoresistant posttraumatic stress disorder (PTSD) and comorbid major depressive disorder (MDD). We recently demonstrated that response to 5 Hz TMS administered to the dorsolateral prefrontal cortex was predicted by functional connectivity of the medial prefrontal (MPFC) and subgenual anterior cingulate cortex (sgACC). This functionally‐defined circuit is a novel target for treatment optimization research, however, our limited knowledge of the structural pathways that underlie this functional predisposition is a barrier to target engagement research. Methods: To investigate underlying structural elements of our previous functional connectivity findings, we submitted pre‐TMS diffusion‐weighted imaging data from 20 patients with PTSD and MDD to anatomically constrained tract‐based probabilistic tractography (FreeSurfer's TRActs Constrained by UnderLying Anatomy). Averaged pathway fractional anisotropy (FA) was extracted from four frontal white matter tracts: the forceps minor, cingulum, anterior thalamic radiations (ATRs), and uncinate fasciculi. Tract FA statistics were treated as explanatory variables in backward regressions testing the relationship between tract integrity and functional connectivity coefficients from MPFC and sgACC predictors of symptom improvement after TMS. Results: FA in the ATRs was consistently associated with symptom improvement in PTSD and MDD (Bonferroni‐corrected p  < .05). Conclusion: We found that structural characteristics of the ATR account for significant variance in individual‐level functional predictors of post‐TMS improvement. TMS optimization studies should target this circuit either in stand‐alone or successive TMS stimulation protocols.